Depois do e- e do b-, o m- e o u-( learning) : uma breve incursão pelos paradigmas emergentes da educação à distância - Lima, Rui Guimarães (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
Some of the most recent approaches in the research field of the History of Education cannot be dissociated from the perspectives provided by distance learning, and still more precisely, from the innovative, emergent and specific methodologies of electronic learning (e-learning), blended (b-learning), mobile or ubiquitous learning (m-learning or u-learning). Definitely, the growing trend of digitization of the pedagogical-didactical contents used in teaching and learning processes, as well as the increasing use of learning management systems and virtual learning environments, have contributed decisively to the relevance of those have been taking in different educational and training contexts. Consequently, in the present paper we will review the literature in order to define and distinguish, in a theoretical and critical point of view, e-learning from b-learning, as well as the m-learning from u-learning, analyzing, simultaneously, some of the newer national and international perspectives in this research field. We also will use it to indicate a significant number of relevant references as way to this paper become a core resource for the implementation and promotion of future researches.